Answer

Verified

414k+ views

**Hint:**We will first find the value of $t$ from the given value of $x$, then will substitute the value in the equation of $y$ involving $t$. Similarly, find the value of $s$ from one equation and substitute in another to get an equation of $x$ and $y$. Solve the two equations to determine the values of $x$ and $y$.

**Complete step-by-step answer:**First of all, we will find the value of $t$ from the given equation $y = 2t$

Then, $t = \dfrac{y}{2}$

Substitute the value of $t$ in the equation of $x$, that is $x = {t^2} + 1$

Therefore, now we have $x = {\left( {\dfrac{y}{2}} \right)^2} + 1$

On simplifying, we get,

\[x = \dfrac{{{y^2}}}{4} + 1\]

\[x = \dfrac{{{y^2} + 4}}{4}\] (1)

Similarly, we will find the value of $s$ from the equation $y = \dfrac{2}{s}$

Now, we will get $s = \dfrac{2}{y}$

Next, we will substitute the value of $s = \dfrac{2}{y}$ in the equation $x = 2s$ to find the value of $x$.

Then, we have

\[x = 2\left( {\dfrac{2}{y}} \right)\]

\[ \Rightarrow x = \dfrac{4}{y}\]

\[ \Rightarrow xy = 4\] (2)

Now, we will equate equations (1) and (2) we will get,

\[\left( {\dfrac{{{y^2} + 4}}{4}} \right)y = 4\]

Hence, on solving the equation we get,

\[y\left( {{y^2} + 4} \right) = 16\]

Now, we add and subtract \[4y\] in the bracket to complete the square and hence solve further,

$

y\left( {{y^2} + 4 - 4y + 4y} \right) - 16 = 0 \\

y{\left( {y - 2} \right)^2} + 4{y^2} - 16 = 0 \\

$

Now we will take terms common and simplify,

$

y\left( {y - 2} \right)\left( {y - 2} \right) + 4\left( {{y^2} - 4} \right) = 0 \\

\Rightarrow y\left( {y - 2} \right)\left( {y - 2} \right) + 4\left( {y + 2} \right)\left( {y - 2} \right) = 0 \\

\Rightarrow \left( {y - 2} \right)\left( {{y^2} - 2y + 4y + 8} \right) = 0 \\

\Rightarrow \left( {y - 2} \right)\left( {{y^2} + 2y + 8} \right) = 0 \\

$

We will equate each of the factors to 0 and find the value of $y$

That is, when $y - 2 = 0$

We get, $y = 2$

Similarly, when we put \[{y^2} + 2y + 8 = 0\]

We will first calculate \[D\] which is \[4ac\]

Hence, we have

$

D = {b^2} - 4ac \\

\Rightarrow D = {\left( 2 \right)^2} - 4\left( 1 \right)\left( 9 \right) \\

\Rightarrow D = 4 - 36 \\

\Rightarrow D = - 34 \\

$

Since, \[D < 0\], there does not exist any real root corresponding to the factor \[{y^2} + 2y + 8\]

Therefore, the value of $y$ is 2

Now, we will substitute the value of $y$ in equation (2) to find the value of $x$

Thus,

$

x\left( 2 \right) = 4 \\

x = 2 \\

$

Hence, the required point is $\left( {2,2} \right)$

**Thus, option B is correct.**

**Note:**Parametric equations are a set of equations that represent the variables as a function of an independent variable. Since, there are two sets of equations involving two parameters, two equations will be formed. And the point of the intersection of the equations is the solution of the two equations.

Recently Updated Pages

Select the smallest atom A F B Cl C Br D I class 11 chemistry CBSE

Cryolite and fluorspar are mixed with Al2O3 during class 11 chemistry CBSE

The best reagent to convert pent 3 en 2 ol and pent class 11 chemistry CBSE

Reverse process of sublimation is aFusion bCondensation class 11 chemistry CBSE

The best and latest technique for isolation purification class 11 chemistry CBSE

Hydrochloric acid is a Strong acid b Weak acid c Strong class 11 chemistry CBSE

Trending doubts

The provincial president of the constituent assembly class 11 social science CBSE

Gersoppa waterfall is located in AGuyana BUganda C class 9 social science CBSE

One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE

Difference Between Plant Cell and Animal Cell

Give 10 examples for herbs , shrubs , climbers , creepers

The hundru falls is in A Chota Nagpur Plateau B Calcutta class 8 social science CBSE

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE